Pelatihan Imam Dan Khatib Bagi Remaja Masjid Di Desa Gunung Melayu Kecamatan Rahuning Kabupaten Asahan - Lakum (peduli riset dan pengabdian masyarakat, 2022)
In Gunung Melayu Village, Rahuning District, there are four mosques, namely Al Yakin Mosque, Al Magfirah Mosque, Al Falah Mosque & Ulil Al Bab Mosque. One of the important da'wah & worship activities to continue to be developed & trained is to become a preacher and imam, especially for the younger generation as regeneration and replacement for the elderly. The existing condition is that in each of these mosques there are 4-5 active youths in the mosque whose roles are only limited to muezzins and occasionally become preachers and imams. Based on observations, it turns out that there are still errors and irregularities in the procedure for giving sermons, the lack of human resources from youth/young people who can give sermons/speech because there is a need for training for preachers and imams, especially for the youth of the mosque. This activity is carried out using the lecture method and direct practice in the field whose material consists of sermon rhetoric, the terms and pillars of the sermon with its series as well as the requirements and etiquette of becoming a priest. Each participant was given the opportunity to perform and practice on the pulpit followed by becoming a priest. This training is especially useful for mosque youth and the younger generation of Islam, especially in terms of increasing knowledge and skills in preaching or giving speeches, the availability of young preachers and young imams of mosques and can be applied especially to mosque youth related to preachers & imams.